2006
DOI: 10.2174/156720506776383013
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Effect of the Apolipoprotein E Genotype on the Lipid Profile in Alzheimers Disease

Abstract: ApoE gene status has minimal influence on the lipid panel or mean age in AD. Apo E gene dose does influence the lipid panel with Apo E 2/2, and 2/3 having significantly better lipid panels and older age of onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…There have also been reports from three prospective studies assessing the effect of statins on cognitive function in younger individuals at risk of heart disease [1][2][3], and two randomized placebo controlled pilot studies testing a statin for benefit in the treatment of AD [4,5]. In the study testing atorvastatin as a treatment for AD it was shown reduced cholesterol levels occurred in advance of clinical benefit [6], and that greater clinical benefit was identified among those patients harboring the ApoE-4 genotype [7], which is known to increase both the risk of AD and circulating cholesterol levels [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…There have also been reports from three prospective studies assessing the effect of statins on cognitive function in younger individuals at risk of heart disease [1][2][3], and two randomized placebo controlled pilot studies testing a statin for benefit in the treatment of AD [4,5]. In the study testing atorvastatin as a treatment for AD it was shown reduced cholesterol levels occurred in advance of clinical benefit [6], and that greater clinical benefit was identified among those patients harboring the ApoE-4 genotype [7], which is known to increase both the risk of AD and circulating cholesterol levels [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, no significant differences were noted in total cholesterol, HDL, total cholesterol to HDL ratio or triglyceride levels 17 . ApoE4 heterozygotes were also noted to have higher HDL levels and lower total cholesterol to HDL ratios when compared to ApoE4 homozygotes.…”
Section: 5 Discussionmentioning
confidence: 69%
“…Past studies have shown that ApoE4 carriers have significantly greater mean LDL when compared to ApoE4 negative individuals 17 . However, no significant differences were noted in total cholesterol, HDL, total cholesterol to HDL ratio or triglyceride levels 17 .…”
Section: 5 Discussionmentioning
confidence: 99%
“…Past studies have shown that APOE ε4 carriers have significantly greater mean LDL compared with APOE ε4-negative individuals [17]. However, no significant differences were noted in total cholesterol, HDL, total cholesterol to HDL ratio, or triglyceride levels [17].…”
Section: Discussionmentioning
confidence: 98%